History of the Paris Commune of 1871 - Lissagaray, Prosper (London Verso, 2012)
From the preface: "The history of the Third Estate was to have been the prologue to this history. But time presses; the victims are gliding into their graves; the perfidies of the Radicals threaten to surpass the worn-out calumnies of the Monarchists. I limit myself for the present to the strictly necessary introduction. Who made the Revolution of the 18th March? What part was taken by the Central Committee? What was the Commune? How comes it that 100,000 Frenchmen are lost to their country? Who is responsible? legions of witnesses will answer. No doubt it is an exile who speaks, but an exile who has been neither member, nor officer, nor functionary of the Commune; who for five years has sifted the evidence; who has not ventured upon a single assertion without accumulated proofs; who sees the victor on the look-out for the slightest inaccuracy to deny all the rest; who knows no better plea for the vanquished than the simple and sincere recital of their history. This history, besides, is due to their children, to all the workingmen of the earth. The child has the right to know the reason of the paternal defeats, the Socialist party the campaign of its flag in all countries. He who tells the people revolutionary legends, he who amuses therewith sensational stories, is as criminal as the geographer who would draw up false charts for navigators."
Includes bibliographical references and index.
Keywords: Paris (France)--History--Commune, 1871.